Congruences of factor solutions of quantitative indicators for understanding the written form of deaf children’s communication through the use of words types - Salkić, Naim; Povlakić Hadžiefendić, Meliha (Technium Social Sciences Journal, 2024)
In deaf students, there is no contextual understanding and recognition of word types through linguistic competence testing compared to the hearing population, because 67.10% do not understand, and 10.00% of deaf respondents partially understand the contextual application of word types in a written text task. In written communication, deaf students use nouns (65.70%), pronouns (34.30%), verbs (45.7%), adjectives (28.60%), adverbs (22.90%), prepositions (54.30%), exclamations (15.70%), particles (12.90%) and numbers (32.90%). The aim of the study was to examine the factor solutions of quantitative indicators of contextual understanding of the word’s types used and the relation of isolated factors of the words types words in the written text task of deaf students. The study was conducted on a sample of 140 respondents. The first subsample of respondents, the experimental group consisted of 70 deaf students, and the second subsample, the control group of 70 hearing students, of the same chronological age and gender. The measurement instrument “Test of comprehension of the written form of expression” was applied. The collected data were processed using the method of oblique rotation and the method of factor analysis. The results of the study showed that the language discourse of the deaf in the quantitative use of word types in the written form of expression is organized significantly differently compared to the hearing population. By factor analysis, three main factors were isolated in the deaf population, and four main factors were isolated in the hearing population. Considering the saturation of variability, it is possible to accurately determine in practice the direction of teaching deaf children the types of words in their native language. Isolated factors are part of separate, statistically unrelated entities in both deaf and hearing respondents and confirm the justification of successive teaching of the deaf respondents according to the types of words that are present in the comparative analysis of hearing respondents.